2022
DOI: 10.1093/jxb/erac309
|View full text |Cite
|
Sign up to set email alerts
|

The small subunit of Rubisco and its potential as an engineering target

Abstract: Rubisco catalyses the first rate-limiting step in CO2 fixation and is responsible for the vast majority of organic carbon present in the biosphere. The function and regulation of Rubisco remain an important research topic and a longstanding engineering target to enhance the efficiency of photosynthesis for agriculture and green biotechnology. The most abundant form of Rubisco (Form I) consists of eight large and eight small subunits, and is found in all plants, algae, cyanobacteria, and most phototrophic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 171 publications
(249 reference statements)
1
17
0
Order By: Relevance
“…Over the past few years this assumption is largely thought to be true because (i) the active site is encoded by the RbcL sequence, and (ii) the RbcL sequence is largely conserved over time as chloroplast-encoded genes evolved slower than nuclear-encoded genes ( Kelly, 2021 ). It is now well established that the Rubisco small subunit encoded by the RbcS gene can influence catalysis too ( Spreitzer et al , 2005 ; Genkov and Spreitzer, 2009 ; Atkinson et al , 2017 ; Martin-Avila et al , 2020 ; Lin et al , 2021 ; Sakoda et al , 2021 ; Mao et al , 2022 ). It would be interesting to see if incorporating RbcS sequences alongside RbcL sequences could improve the predictive power of our models.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years this assumption is largely thought to be true because (i) the active site is encoded by the RbcL sequence, and (ii) the RbcL sequence is largely conserved over time as chloroplast-encoded genes evolved slower than nuclear-encoded genes ( Kelly, 2021 ). It is now well established that the Rubisco small subunit encoded by the RbcS gene can influence catalysis too ( Spreitzer et al , 2005 ; Genkov and Spreitzer, 2009 ; Atkinson et al , 2017 ; Martin-Avila et al , 2020 ; Lin et al , 2021 ; Sakoda et al , 2021 ; Mao et al , 2022 ). It would be interesting to see if incorporating RbcS sequences alongside RbcL sequences could improve the predictive power of our models.…”
Section: Discussionmentioning
confidence: 99%
“…In plants the RbcL subunit of Rubisco is encoded by the chloroplast DNA (plastome) and is synthesized in the chloroplast stroma, while the nuclear encoded RbcS (1 to 25 paralogs, plant species dependent [3]) is translated in the cytosol and imported into the chloroplast [4,6].…”
Section: Rubisco Biogenesis -Folding and Assemblymentioning
confidence: 99%
“…improve crop yields (food security) [1][2][3][4] and lessen the greenhouse effect of atmospheric CO 2 [5]. Here we discuss two strategies that aim to screen for improved catalytic properties of Rubisco, namely directed evolution (DE) and/or computational protein design.…”
Section: Engineering Catalytic Properties Of Rubiscomentioning
confidence: 99%
“…The assembly of functional Form IB Rubisco in plants requires cognate chaperones that are likely species specific; for example, up to seven cognate chaperones are involved in Rubisco assembly in Arabidopsis thaliana ( Aigner et al, 2017 ). Moreover, the large and small subunits of plant Rubisco are encoded in disparate locations: the plant Rubisco large subunit RbcL is encoded by a single rbcL gene in the chloroplast genome, whereas the small subunit RbcS, which plays a vital role in regulating Rubisco content ( Mao et al, 2022 ), is encoded by multiple rbcS genes in the nuclear genome. All these factors unambiguously increase the complexity of engineering and modifying Rubisco in plants ( Whitney et al, 2011a ; Martin-Avila et al, 2020 ) and may contribute to the observed lower yields of exogenous Rubisco in transgenic lines (∼10% of the Rubisco content of the wild-type [WT]) ( Lin et al, 2014 ; Long et al, 2018 ; Orr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%